The Effect Of Return On Asset (Roa) And Dividend Policy On The Value Of Manufacturing Companies - Nunuk Novianti; Indra Wijaya Indra Wijaya; Ani Febianingsih Ani Febianingsih (Al-Makki Publisher, 2022)
The purpose of this research is to know how much influence of Return on Assets (ROA) and Dividend Policy to Firm Value partially on Manufacturing Companies. The method of data collection is through the population data of manufacturing companies for the period 2017 to 2021. The data is taken through the official website of the Indonesia Stock Exchange (www.idx.co.id). The total population was found to be 167 listed companies. The samples of companies used in this study are twenty seven companies that have passed the criteria that have been determined in purposive sampling. In this study, the data used is secondary data. To obtain secondary data, it is taken from financial reports, annual reports and sustainability reports of each manufacturing company listed on the Indonesia Stock Exchange. Data processing using IBM SPSS 25 application.